Obelia bidentata Clark 1875 ... - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
Obelia bidentata Clark, 1875 (*) Obelia bidentata —Peña Cantero et al., 2013: 749, fig. 9g, h. Distribution. Worldwide. In the Ross Sea, known from Tethys Bay (Peña Cantero et al. 2013). ... : Published as part of ÁLVARO L. PEÑA CANTERO, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa, pp. 1-65 in Zootaxa 4293 (1) on page 27, DOI: 10.11646/zootaxa.4293.1.1, http://zenodo.org/record/828475 ...